Screening and validation of key microRNAs regulating muscle development in Hanper sheep - Yunxia Zhi; Boxin Hu; Shujun Tian; Ying Bai; Xiaoyong Chen (PLoS ONE, 2025)
Background/Objectives In sheep farming, the economic significance of meat characteristics is substantial, and advancing the genetic quality of livestock relies heavily on understanding the cellular mechanisms behind muscle growth and its regulation. This study examined miRNA expression patterns in the longissimus dorsi muscle tissue of Hanper sheep of various ages, with the goal of determining their biological functions and identifying miRNAs and their target mRNAs that influence muscle development and meat quality. Methods Using the Image-Pro Plus 6.0 program and HE and fluorescent staining procedures, we measured the diameter of muscle fibers in the longissimus dorsi of Hanper sheep at three distinct ages (1, 7, and 13 months) in order to calculate the average fiber size. For the analysis of muscle fiber area, one-way Analysis of Variance was conducted using Statistical Package for the Social Sciences 25.0, with Least Significant Difference tests applied afterward to compare the different groups. Transcriptome sequencing was conducted to identify miRNAs, and bioinformatics tools were applied to predict their target genes. GO and KEGG functional annotations were used to analyze the biological functions of these target genes. RT-qPCR was performed to validate the expression levels of differential expressed miRNAs. Results Muscle fiber diameter and area increased progressively with age, as indicated by HE and fluorescence staining. Four novel miRNAs identified for the first time in sheep were among the 116 differential expressed miRNAs that were found. These miRNAs were found to be involved in key pathways such as TGF-β, mTOR, Wnt, and MAPK, which regulate muscle growth and development. It was determined that three new miRNA-mRNA pairs included oar-miR-133/MSC, oar-miR-148a/FST, and oar-miR-410-3p/NIN may be essential for muscle growth. RT-qPCR results confirmed the expression trends observed in the transcriptome sequencing data. Conclusions Our knowledge of the fundamental molecular mechanisms underpinning muscle growth and development is improved by the discovery of new miRNAs and the target genes that correspond to them. These findings may serve as new breeding targets for improving meat quality in sheep.